Canadian Thoracic Society Guidelines for Occupational Asthma - Susan M Tarlo; Louis-Philippe Boulet; André Cartier; Donald Cockcroft; Johanne Côtè; Frederick E Hargreave; Linn Holness; Gary Liss; Jean-Luc Malo; Moira Chan-Yeung (Canadian Respiratory Journal)
OBJECTIVE: To provide broad guidelines and principles to help primary care physicians, occupational physicians, allergists and respirologists with the recognition, diagnosis and management of patients with occupational asthma (OA).